2015
DOI: 10.1039/c5py01241d
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable pH-regulated supramolecular copolymerisation by mixing mismatched dendritic peptide comonomers

Abstract: The co-assembly of oppositely charged phenylalanine-rich dendritic comonomers yields supramolecular alternating copolymers, whose stability and pH-triggered disassembly is tuned by mismatching a strong with a weak β-sheet encoded comonomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 55 publications
0
42
0
1
Order By: Relevance
“…Angewandte Chemie Zuschriften 10.5;Scheme 1) as it is fully protonated at both pH values;the resulting charge repulsion leads to unfolding of the structure. [11] Theo btained hydrogel is mechanically quite stable as confirmed by rheology studies (Table S2 and Figure S6). Upon decreasing the pH value to pH 4, at which the GCP moieties are protonated, the particle size was significantly reduced (only 28 nm at 100 mm).…”
mentioning
confidence: 60%
“…Angewandte Chemie Zuschriften 10.5;Scheme 1) as it is fully protonated at both pH values;the resulting charge repulsion leads to unfolding of the structure. [11] Theo btained hydrogel is mechanically quite stable as confirmed by rheology studies (Table S2 and Figure S6). Upon decreasing the pH value to pH 4, at which the GCP moieties are protonated, the particle size was significantly reduced (only 28 nm at 100 mm).…”
mentioning
confidence: 60%
“…The C 3 ‐symmetrical dendritic peptide comonomers 1 and 2 were synthesized using a previously reported convergent synthetic approach ( Figure 1 A) . We first employed standard Fmoc solid‐phase peptide synthesis to prepare a Fmoc‐NH‐Phe‐His‐Phe‐His‐Phe‐OH peptide 3 .…”
Section: Resultsmentioning
confidence: 99%
“…To this end we have disclosed an ampholytic supramolecular copolymer design, whereby the multicomponent coassembly of anionic oligo(glutamic acid ‐alt‐ phenylalanine) and cationic oligo(lysine ‐alt‐ phenylalanine) peptide synthons leads to alternating copolymer formation . The pH‐stability window of these copolymers could be tuned by a supramolecular engineering approach, using mismatched comonomer pairs which shifts the pH‐triggered disassembly of the copolymers from pH 4.2 to 5.8 . In this case however the pH‐triggered glutamic acid monomer that is released upon disassembly of the copolymers leads to the formation of homopolymers, in a process that is driven by charge regulation.…”
Section: Introductionmentioning
confidence: 99%
“…[273][274][275][276][277][278][279][280][281][282][283][284][285][286][287][288] One-dimensional alternating supramolecular copolymers with a nanorod-like morphology are obtained, via a combination of attractive Coulomb interactions, hydrogen bonding, and hydrophobic shielding. [289][290][291] In pHdependent characterization experiments, it was shown that the charges in the ampholytic copolymers are screened by either protonating the carboxylate or deprotonating the ammonium groups in the side chains of the comonomers, which leads to the disassembly of the copolymers at pH 5 3.6 and pH 5 8.9. Experimental characterization of the supramolecular structures included CD spectroscopy, 13 C CP-MAS NMR, TEM, as well as multiscale molecular modeling.…”
mentioning
confidence: 99%
“…291 The coassembly of a longer hexapeptidic, stronger b-sheet comonomer, with a second weaker pentapeptidic b-sheet design shifted the pH-triggered disassembly for the copolymers from pH 4.2 for the two strong b-sheet synthons to biologically relevant pH 5.8 for the mismatched pair between a strong cationic and a weak anionic b-sheet monomer. 291 Importantly, the stability towards the addition of NaCl was not compromised. These tuneable pH-triggered polymers will open new avenues for applications in biomedical technologies, for example as drug and gene delivery vehicles, where the release of cargo material in intracellular compartments is generally assumed to be regulated by both a decrease of the pH and by osmotic swelling.…”
mentioning
confidence: 99%